THE EFFECT OF PRIVACY PERCEPTION AND SECURITY PERCEPTION ON CUSTOMER LOYALTY WITH TRUST AS AN INTERVENING VARIABLES IN ZALORA E-COMMERCE (A Case Study of Zalora Users in Yogyakarta City) - Rudi Kurniawan; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
A business using the internet will have a great opportunity to develop. Business activity through popular internet media is called electronic commerce (e-commerce). There are lots of e-commerce that offer various kinds of goods needed by consumers. Starting from daily necessities or other additional items are widely offered in online shops. Some online shopping sites are even favored and have good ratings by consumers, one of which is Zalora Indonesia. This study aims to determine (1) the effect of Perceptions of Privacy on Trust (2) the effect of Perceptions of Security on Trust (3) the effect of Trust on Loyalty. The sample in this study was 100 respondents from the city of Yogyakarta who had shopped using the Zalora Indonesia e-commerce. The data collection method uses a questionnaire that is distributed using a purposive sampling technique. This study using the Data Quality Test, Classical Assumption Test, Multiple Regression Test, and Hypothesis Test. The results of this study indicate (1) there is a positive and significant influence on Perceived Privacy on Trust (2) there is a positive and significant effect on Perceived Security on Trust (3) there is a positive and significant effect of Trust on Loyalty.